HBR guide to crafting your purpose - Coleman, John, 1981- (Harvard business review guides., 2022)
"Stop searching for purpose. Build it. We're living through a crisis of purpose. Surveys indicate that people feel less and less connected to the meaning of their work. Individuals everywhere are asking, "How can I find my purpose?" That's the wrong question. You don't find your purpose-you build it. The HBR Guide to Crafting Your Purpose debunks three misconceptions about purpose at work: that purpose is found, that you have only one, and that it remains the same over time. Packed with tips and advice for how you can cultivate more meaning in your life and at work, this book teaches you how to endow everything you do with purpose each day. You'll learn how to: find the reason behind your work, identify what makes you feel happy and engaged, use job crafting to transform your role, connect your work to service, build positive, fulfilling relationships, let go of past purposes-and take steps toward new ones, arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges"--